Assessment of immunological and hematological parameters in Blastocystis species-infected chronic leukemic patients - Heba Elhadad; Bassam Mohamed Abdel-Fattah; Sally A. M. Saleh; Moustafa Abo El-Hoda; Hend El-Taweel (Gut Pathogens)
Abstract Aim Blastocystis spp. is a common intestinal protozoan with controversial pathogenicity. It is frequently associated with gastrointestinal (GIT) disturbances and is particularly prevalent among immunocompromised individuals. This study aimed to assess the prevalence of Blastocystis spp. infection and its association with immunological and hematological parameters among chronic leukemic patients. Methods Stool and blood samples were collected from 100 chronic leukemic patients. Microscopic examination and a coproantigen assay were performed for the detection of Blastocystis spp., along with assessment of anti-Blastocystis fecal IgA and serum IgG antibodies. CD4 T cells and the serum level of IL-8 were also measured. Results The overall Blastocystis spp. infection rate was 60%, determined through combined microscopy and/or coproantigen detection. Among infected patients, anti-Blastocystis IgA was positive in only three patients and IgG in 18 patients, with no statistically significant association between Blastocystis spp. infection and detection of antibodies. Infection was significantly associated with elevated IL-8 levels and WBC count. There was no statistically significant association between the presence of gastrointestinal symptoms and the levels of anti-Blastocystis IgG or IgA, IL-8, or CD4 count in Blastocystis spp.-infected patients. Conclusion Our study reveals a high prevalence of Blastocystis spp. infection among chronic leukemic patients and identifies a significant association between infection and elevated IL-8 levels.